Haemophilus Parainfluenzae mural endocarditis with large atrial septal defect and peripheral embolization. Issue 3 (March 2022) - Bae, Ju Young; Murugiah, Karthik; McLeod, Gavin X.; Anwer, Muhammad; Howes, Christopher J.
Abstract: Mural endocarditis is a rare subclass of infective endocarditis (IE) associated with intra-cardiac tumors, prosthesis, valvular vegetation's, or structural abnormalities such as ventricular septal defects. Bacteria classified as HACEK ( Haemophilus species, Aggregatibacter actinomycetemcomitans, Cardiobacterium hominis, Eikenella corrodens, and Kingella kingae ) are rare causes of IE found in only 1.3% to 10% of cases. We describe the second reported case of mural endocarditis involving the left ventricle (LV) caused by a Haemophilus species. A young male with no prior intravenous drug use, valvular heart disease, or recent dental work presented with splenic infarcts. H. para-influenza was identified on blood cultures. Cardiac imaging revealed a 1.5 cm LV mass underneath the posterior leaflet of the mitral valve and a large Atrial Septal Defect (ASD). Awaiting surgery, the patient sustained embolic and hemorrhagic cerebral events. The patient underwent debulking of LV mass, ASD closure, and mitral valve repair complicated by post-pericardiotomy syndrome, and he completed six weeks of ceftriaxone therapy. The patient met modified Duke Criteria, but the diagnosis was challenging due to absence of risk factors, sub-acute symptom onset, delayed blood culture growth, and ambiguous characterization of the mass on imaging. <Learning objective: To recognize mural endocarditis as a distinct subset of infective endocarditis and understand its risk factors. To appreciate the unique diagnostic and prognostic considerations of HACEK endocarditis. To understand the indications for urgent surgical intervention in treatment of infective endocarditis>